Evaluation of The Implementation of Inclusive Education in Magetan - Gina Solihat (Indonesian Journal of Disability Studies, 2018)
This study aims to evaluate the inclusion of inclusive education in Magetan. This research is a descriptive quantitative research conducted on 5 elementary and middle school providers of inclusive education in Magetan. The sampling technique uses purposive random sampling. Data collection technique in this research is using questionnaire in the form of Self Evaluation Instrument Inclusion School developed by Yusuf (2014). Data analysis technique is using descriptive statistics. The results show that inclusive education in Magetan is classified as a good criterion where there is an average of 64% of 9 dimensions of inclusive education in accordance with the standard with the following details: Institutional aspect 74% (good), curriculum aspect 83% (excellent), 60% and good (60%), 60% (good), 58% (medium), 51% human resources aspect 58% (medium), facilities and infrastructure aspects 17% (very less), community participation aspect 63% (good), and financing aspects 46% (medium).